2022
DOI: 10.1002/hec.4505
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for developing a lifecycle, multidimensional assessment framework for mobile medical apps

Abstract: The COVID-19 pandemic has unquestionably accelerated the transition to digital health (DH) (Pandey & Pal, 2020;Petracca et al., 2020). More specifically, mobile apps have given health care systems the opportunity to support public health surveillance during the most hard-hit periods, at once emphasizing the need to picture and build cutting-edge care models for the upcoming future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…However, the evidence base for coverage decisions is a frequently and highly discussed topic. Increasingly, models are being developed to evaluate DiHA [16][17][18] also due to methodological gaps and difficulties in assessing the value of DiHA, including the question for an adequate control group to be included in clinical trials and the level of evidence to be used [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence base for coverage decisions is a frequently and highly discussed topic. Increasingly, models are being developed to evaluate DiHA [16][17][18] also due to methodological gaps and difficulties in assessing the value of DiHA, including the question for an adequate control group to be included in clinical trials and the level of evidence to be used [19].…”
Section: Introductionmentioning
confidence: 99%
“…More common and less urgent situations can be covered even with the vignette study. Finally, although the production of research data was slowed down by the COVID-19 pandemic [54,55], the number of individual users of mobile medical apps and Omaolo.fi grew exponentially during the pandemic [56][57][58].…”
Section: Strengths and Weaknessesmentioning
confidence: 99%
“…In this supplement, Tarricone et al. analyzed current assessment frameworks for digital technologies and concluded that none is sufficiently complete as to encompass all relevant domains for regulatory, policymaking, HTA and coverage purposes (Tarricone et al., 2022). The authors identified 10 principles that would need to inspire assessment frameworks based on a life‐cycle evidence generation approach for mHealth apps.…”
Section: Research Aim 1: Improving the Evaluation Of Medical Devicesmentioning
confidence: 99%